The role of Symbiodinium membrane lipids in response to heat shock: implications for coral bleaching - Botana, Marina Tonetti (2019)
Coral reefs around the world have been largely devastated by the phenomenon of \"coral bleaching\", which causes have been reported to be strongly related to oxidative stress promoted by climate change drivers, including mainly global warming and catastrophic El Niño events. Genetic variability in coral endosymbionts from the Family Symbiodiniacea was also suggested as determinant of host susceptibility to stress because they present distinct physiological boundaries when in free living or in symbiosis. Here we present for the first time the successful use of lipidomics (i.e. , the global characterization of lipids in a given organism) supporting molecular investigation in the oxidative mechanisms related to thermal stress in coral endosymbionts phylotypes. Symbiodinium minutum was thermal sensitive, whereas S. microadriaticum and S. goreaui presented different levels of thermal tolerance. Their lipid phenotypes after stress, including the photosystem electron transporter - plastoquinone - suggested they had different survival strategies. In addition, chloroplast specific lipids with polyunsaturated fatty acids (PUFAs) mainly formed by omega 3 (n-3) seemed to be essential to sustain Symbiodinium cells bioenergetics in the long term (10 days after stress). S. microadriaticum and S. goreaui capability of keeping high n-3 concentrations in the chloroplast membranes determined their survival. The present thesis reports, for the first-time, upregulation of oxidized lipids derived from precursor chloroplast membranes and free fatty acids (FFA) in response to oxidative stress damage caused by heat. The study of lipid membranes is of paramount importance to better understand the bioenergetics of symbionts and to determine the host/endosymbiont vulnerability to climate change stressors in a warmer future.